Social Exclusion as Spiritual Inclusion: Collective Identity-Making and Urban Theology in Faith-Based Food Assistance in Finland - Huotari, Rosa (Journal of empirical theology, 2023)
Through ethnographic fieldwork conducted in 2020–2021, this paper investigates how people experiencing poverty and social exclusion process their collective in-group/ out-group identity as the urban ‘others’ in faith-based food assistance in Finland. By building on the concept of collective identity and employing narrative construction, the analysis shows that not only does perceived social exclusion function as a stigmatizing self-category and symbolic boundary maker but also as a resource for resistance, especially in the theological accounts of the informants. When looking through the lenses of urban theology, the informants do not just tell a story about themselves, but they do theology as well. All in all, the others may be excluded from society and yet included in Spirit.